Pemanfaatan Kecerdasan Buatan Untuk Transformasi Pembelajaran Di Era Digital - Wutsqo, Minnaty Adhimatul (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2024)
The transformation of learning in the digital era requires innovations that can address the challenges of globalization and technological advancement. This article discusses the utilization of Artificial Intelligence (AI) as a catalyst in transforming traditional learning paradigms into more personalized, interactive, and data-driven experiences. AI technologies such as adaptive learning, educational chatbots, voice recognition, and learning analytics enable educators to provide learning experiences tailored to the individual needs of students. Additionally, AI can enhance the efficiency of educational administration, expand access to learning resources, and support global collaboration. Through literature review and practice analysis, this article offers strategic recommendations for effective and inclusive AI implementation in education. The findings are expected to provide insights for stakeholders to promote sustainable educational innovation in the digital era.